2017
DOI: 10.1007/s00253-017-8241-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics and scale-up of Agrobacterium tumefaciens

Abstract: Production of recombinant proteins in plants through Agrobacterium-mediated transient expression is a promising method of producing human therapeutic proteins, vaccines, and commercial enzymes. This process has been shown to be viable at a large scale and involves growing large quantities of wild-type plants and infiltrating the leaf tissue with a suspension of Agrobacterium tumefaciens bearing the genes of interest. This study examined one of the steps in this process that had not yet been optimized: the scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…A few additional considerations regarding the use of defined media: this media is more economical in terms of material cost, but the labor cost of preparation may be higher since there are more steps required. The overall ionic character of the defined media is also a consideration, as higher ionic strength may correspond to higher cell maintenance costs, and previous work has indicated that Agrobacterium grown in chemically defined media may be more sensitive to shear stress . In this study sucrose and ammonium concentration were observed to have a negative effect on final biomass concentration, but higher biomass concentrations may be possible if the concentration of these nutrients can be increased without this negative effect.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…A few additional considerations regarding the use of defined media: this media is more economical in terms of material cost, but the labor cost of preparation may be higher since there are more steps required. The overall ionic character of the defined media is also a consideration, as higher ionic strength may correspond to higher cell maintenance costs, and previous work has indicated that Agrobacterium grown in chemically defined media may be more sensitive to shear stress . In this study sucrose and ammonium concentration were observed to have a negative effect on final biomass concentration, but higher biomass concentrations may be possible if the concentration of these nutrients can be increased without this negative effect.…”
Section: Discussionmentioning
confidence: 65%
“…With no supplemental sugars added to LB or YEP media the most abundant nutrient source available in these media is amino acids. To determine if certain amino acids were preferentially consumed, free amino acid concentration was measured at three points over an Agrobacterium batch growth in LB media grown at a 5 L scale . Measurements were taken on media directly before inoculation (0 h), during the exponential phase of growth (8 h), and when growth had reached stationary phase (12.5 h) and a final biomass concentration of 3.3 OD 600 (2.0 g DCW/L).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wild-type plant cell suspension cultures in pilot-scale and industrial-scale STBs for the production of plant metabolites have been widely reported (Katō et al, 1972;Noguchi et al, 1977;Schiel & Berlin, 1987;Ulbrich et al, 1985), including Taxus chinensis suspended cells grown in a 75,000-L STB at Phyton Biotech® for the production of paclitaxel, a potent cancer treatment chemical (Imseng et al, 2014). However, the studies of pilot-scale and commercialscale bioreactors for recombinant therapeutic protein productions from transgenic plant cell cultures are scarce, especially in STBs.…”
mentioning
confidence: 99%